Cellulose hydrogel with in-situ confined nanopores for boosting moist-electric conversion - Xuejiao Lin; Shenming Tao; Jilong Mo; Xijun Wang; Yizhe Shao; Yingfan Hu; Changjing Qiu; Kaiyuan Shen; Chao Dang; Haisong Qi (Nature Communications)
Abstract Hydrogels are promising for moist-electric generator, yet their performance is limited by microscale pores, low charge density, and unstable pore structures. Here, a delignified pomelo peel-confined carboxymethyl cellulose nanofluidic hydrogel is designed to address these limitations. Leveraging the hierarchical porous architecture of delignified pomelo peel, the nanofluidic hydrogel achieves sub-Debye-length nanopores with high stability and charge density. At 80% relative humidity, a single device unit exhibits an open-circuit voltage of 1.32 V and a short-circuit current density of 693.2 µA cm-2, which are nearly triple and twenty times higher than delignified pomelo peel. The output voltage exceeds that of conventional hydrogel without nanopores by about 0.4 V. This enhanced performance is due to sub-Debye-length nanopores synergizing H+/Cu2+ gradient diffusion and Debye screening effect. Moreover, the integrated devices reach an ultrahigh output voltage exceeding 5000 V. We report the prototype of a moisture-stimulated negative air ion generator for efficient air purification. This work advances moisture energy harvesting through pore engineering and expands its applications.